EPIDEMIOLOGY OF TURMERIC (CURCUMA LONGA L) LEAF SPOT CAUSED BY COLLETOTRICHUM GLOEOSPORIOIDES (PENZ AND SACC) - S. K. CHAWDA; A. N. SABALPARA; J. R. PANDYA (The Bioscan, 2012)
Young crops (2 to 2.5 months) were mostly remained free from the infectivity of the leaf spot. The infection was started during August and attained its peak on completion of major rainfall i.e. after 37th MSW. During the major progress (37th to 40th MSW), average temperature remained around 28ºC and 80 per cent relative humidity with moderate rainfall. Correlation coefficient study between weather parameters and disease intensity indicated that all the parameters jointly played an important role in the development of disease. The multiple regression equation [Y = 77.39 + 1.04 (X1) – 3.69 (X2) – 0.0000000007 (X3) + 17.32 (X4) + 17.89 (X5) - 35.16 (X6) - 0.014 (X7) – 1.51 (X8) where X1 = Maximum temperature, X2 = Minimum temperature, X3 = Average temperature, X4 = Morning relative humidity, X5 = Evening relative humidity, X6 = Average relative humidity, X7 = Rainfall, X8 = Rainy days] was developed for the forecasting (R=0.81).